Prescribing patterns of medicine classified as 'antidepressants' in South African children and adolescents - Johanita R. Burger; Elmarie van der Westhuizen; Martie S. Lubbe; Jan H. P. Serfontein (AOSIS, 2009)
The main objective of this study was to characterise prescribing patterns of medicine classified as 'antidepressants' (hereafter simply referred to as antidepressants) in children and adolescents in the private health care sector of South Africa. A retrospective drug utilisation design was used to identify patients aged 19 years and younger from a South African pharmaceutical benefit management company's database, whom were issued at least one antidepressant between 1 January 2006 and 31 December 2006. Prescribed daily dosages (PDDs) were calculated using the Statistical Analysis System® program. A total of 1 013 patients received a mean number of 2.88 (SD 3.04) prescriptions per patient. Females received more prescriptions than their male counterparts, with the highest prevalence in the 15 ≤ 19 years age group. The pharmacological groups most prescribed were the selective serotonin reuptake inhibitors (43.0%) and the tricyclics (42.7%), with imipramine (22.04%) and amitriptyline (19%) as the most commonly prescribed drugs. Approximately 30% (n = 2 300) of all antidepressants in the study population were prescribed off-label. Amitriptyline and clomipramine were prescribed at daily dosages higher than recommended in children and adolescents aged 9 ≤ 15 years. Lithium, trimipramine, trazodone and sulpiride were prescribed at sub-therapeutic dosages in adolescents. This study provided insight in the prescribing patterns of medicine classified as antidepressants in South African children and adolescents. These drugs, however, have many indications. Further research is needed to determine reasons why specific drugs are prescribed in this population. Opsomming Die algemene doelstelling van hierdie studie was om die voorskrifpatrone van middels wat as 'antidepressante' geklassifiseer word (hierna verwys na as slegs antidepressante) wat vir kinders en adolessente in die Suid-Afrikaanse private gesondheidsorgsektor voorgeskryf word, te beskryf. 'n Retrospektiewe medisyneverbruiksontwerp is gebruik om pasiënte 19 jaar en jonger, wat in die periode van 1 Januarie 2006 tot 31 Desember 2006 ten minste een voorskrif vir 'n antidepressant ontvang het, in die databasis van 'n Suid-Afrikaanse farmaseutiese voordelebestuursmaatskappy te identifiseer. Voorgeskrewe daaglikse dosisse (VDDs) is bereken deur van die program Statistical Analysis System® gebruik te maak. 'n Totaal van 1 013 pasiënte het 'n gemiddeld van 2.88 (SA 3.04) voorskrifte per pasiënt ontvang. Vroue het meer voorskrifte as hul manlike eweknieë ontvang, met die hoogste voorkoms in die ouderdomsgroep 15 ≤ 19 jaar. Die farmakologiese groepe selektiewe  serotonienherop-nameremmers (43.0%) en die trisikliese antidepressante 42.7%) is die meeste voorgeskryf, met imipramien (22.04%) en amitriptilien (19%) as die mees algemeen voorgeskrewe middels. Ongeveer 30% (n = 2 300) van alle antidepressante in die studiepopulasie is voorgeskryf vir indikasies waarvoor dit nie geregistreer is nie. Amitriptilien en klomipramien is teen daaglikse dosisse hoër as die aanbevole vir 9 ≤ 15-jarige kinders en adolessente voorgeskryf. Litium, trimipramien, trasodoon en sulpiried is teen sub-terapeutiese dosisse vir adolessente voorgeskryf. Hierdie studie het insig verleen ten opsigte van die voorskrifpatrone van middels wat as anti- depressante geklassifiseer word vir Suid-Afrikaanse kinders en adolessente. Hierdie middels het egter baie gebruike. Verdere navorsing word benodig om redes te bepaal waarom sekere middels in hierdie populasie voorgeskryf word.